2014
DOI: 10.1039/c4tc01906g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and transport properties of carbon and boron-nitride ferrocene nanopeapods

Abstract: Electronic and transport properties of novel ferrocene based carbon nanotube (CNT) and boron-nitride nanotube (BNNT) nanopeapods, including Fe(Cp) 2 @CNT, Fe 2 (Cp) 3 @CNT, Fe(Cp) 2 @BNNT, and Fe 2 (Cp) 3 @BNNT (where Cp refers as cyclopentadiene), are investigated using the density functional theory and non-equilibrium Green's function methods. Computed electronic structures of the Fe(Cp) 2 @CNT and Fe 2 (Cp) 3 @CNT nanopeapods suggest that their electric conductivity is primarily contributed by the CNT p cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…[41][42][43][44][45][46][47] Recently, multidecker organometallic sandwich NWs have attracted growing attention owing to their potential applications in molecular electronic and magnetic devices. 68,69 Here, we show that (VBz) n NWs can also be introduced into CNTs or BNNTs to form nanocables with multifunctional properties. 58,59 In particular, a NW system under intensive investigation is the vanadium-benzene multidecker (VBz) n (Bz = C 6 H 6 ) NW.…”
Section: Introductionmentioning
confidence: 81%
“…[41][42][43][44][45][46][47] Recently, multidecker organometallic sandwich NWs have attracted growing attention owing to their potential applications in molecular electronic and magnetic devices. 68,69 Here, we show that (VBz) n NWs can also be introduced into CNTs or BNNTs to form nanocables with multifunctional properties. 58,59 In particular, a NW system under intensive investigation is the vanadium-benzene multidecker (VBz) n (Bz = C 6 H 6 ) NW.…”
Section: Introductionmentioning
confidence: 81%
“…Nanocrystalline HAp is found in natural bone, where nanoscale apatite-like crystals mineralize collagen fibers [1e3]. Along with pristine HAp, HAp with the addition of other inorganic elements such as fluorine [4,5], strontium [6e8], europium [9], yttrium [10] etc., has been used for some specific application such as drug delivery [7,9] and light emitting [5] and luminescence applications [2,8]. Fluor-hydroxyapatite [FHAp; Ca 10 (PO 4 ) 6 (OH,F) 2 ] its fluoridated form, has gained its importance in the area of dental restoration because of its specific biological benefits including the resistance of apatite to resorption by body fluids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al have used a P25-rGO composite, which showed a seven times increase in visible-light photocatalytic activity. [255] The reduction of Cr(VI) with a maximum removal rate of 91% was achieved by the GR-TiO 2 composite under UV-light irradiation. Apart from this, GR-TiO 2 Fig.…”
Section: Graphene-based Tio 2 Photocatalystmentioning
confidence: 95%